2007
DOI: 10.1007/s00787-007-0626-z
|View full text |Cite
|
Sign up to set email alerts
|

Categorical and dimensional aspects of co-morbidity in obsessive-compulsive disorder (OCD)

Abstract: Objective: Obsessive-Compulsive Disorder (OCD) defined at the diagnostic level encompasses divergent symptoms and is often associated with other psychiatric problems.The present study examines OCD versus co-morbid symptom patterns in OCD in children and adolescents in order to investigate the presence of diagnostic heterogeneity Subjects and methods: One-hundred and thirteen outpatients with primary OCD participated.The patients' and primary caretakers' responses on semi-structured interviews (child version of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
71
1
4

Year Published

2011
2011
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(83 citation statements)
references
References 42 publications
3
71
1
4
Order By: Relevance
“…Other studies involving children and adolescents have also observed a higher prevalence of tic disorders in boys. 11,35,38 Conversely, one study has reported a higher frequency of attention deficit hyperactivity disorder in boys, 38 and another has observed more simple phobias, anorexia, compulsive buying, and skin picking in girls. 35 We believe that the small number of boys included in our sample may have affected our results, failing to reveal other significant associations.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies involving children and adolescents have also observed a higher prevalence of tic disorders in boys. 11,35,38 Conversely, one study has reported a higher frequency of attention deficit hyperactivity disorder in boys, 38 and another has observed more simple phobias, anorexia, compulsive buying, and skin picking in girls. 35 We believe that the small number of boys included in our sample may have affected our results, failing to reveal other significant associations.…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, there has been no other study with Asian American adolescents that has examined thought problems of Korean American youth. Although the YSR "thought problems scale" has been linked to a number of psychiatric symptoms and disorders, its relationship to obsessive-compulsive behavior (OCB) may be relevant here (Hudziak et al, 2006;Ivarsson, Melin, & Wallin, 2007). Our findings could reflect a greater emphasis among Korean American adolescents than other adolescents on certain behaviors that are similar to OCB (e.g.…”
Section: Discussionmentioning
confidence: 83%
“…In many research studies, OCD is comorbid with depression and anxiety (Ivarsson, Melin, & Wallin, 2008;Peris et al, 2010). Depression leads to drawback of treatment outcomes for individuals with OCD (Storch et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Depression leads to drawback of treatment outcomes for individuals with OCD (Storch et al, 2008). Anxiety also is more prevalent than depression in OCD (Ivarsson, Melin, & Wallin, 2008;Langley, Lewin, Bergman, Lee, & Piacentini, 2010). The severity of anxiety will be great if the symptoms of OCD increase .…”
Section: Introductionmentioning
confidence: 99%